Flotation therapy for downer cows - Van Metre, D.C.; St. Jean, G.; Vestweber, J. (Kansas Agricultural Experiment Station, 2011)
Cattle that become recumbent (unable to get up) as the result of calving difficulty, low blood calcium, traumatic injuries, or other disorders are prone to develop subsequent pressure damage of muscles, nerves, and areas of skin. The resulting medical problems that are secondary to prolonged recumbency may be more life-threatening than the initial medical disorder that caused recumbency. Flotation therapy is an effective means of physical therapy for rehabilitation of "downer" cattle. A description of flotation therapy and data from the first year of use of the flotation tank at the Veterinary Medical Teaching Hospital, Kansas State University, are presented.
Keywords: Downer cow; Recumbency; Flotation; Physical Therapy